Involvement of cDNA in homologous recombination between Ty elements in Saccharomyces cerevisiae. - Melamed, C (1992)
Strains carrying a marked Ty element (TyUra) in the LYS2 locus were transformed with plasmids bearing a differently marked Ty1 element (Ty1Neo) under the control of the GAL promoter. When these strains were grown in glucose, a low level of gene conversion events involving TyUra was detected. Upon growth on galactose an increase in the rate of gene conversion was seen. This homologous recombination is not the consequence of increased levels of transposition. When an intron-containing fragment was inserted into Ty1Neo, some of the convertants had the intron removed, implying an RNA intermediate. Mutations that affect reverse transcriptase or reverse transcription of Ty1Neo greatly reduce the induction of recombination in galactose. Thus, Ty cDNA is involved in homologous gene conversion with chromosomal copies of Ty elements. Our results have implications about the way families of repeated sequences retain homogeneity throughout evolution.